INTEGRATING BLOCKCHAIN TECHNOLOGY INTO WAQF MANAGEMENT FOR ENHANCED TRANSPARENCY AND GLOBAL SOCIAL INCLUSION - Ryan Teo; Rania Al-Mohammed; James Njoroge; Dodi Setiawan Riatmaja (Yayasan Adra Karima Hubbi, 2026)
The growing demand for transparency and accountability in Islamic social finance has intensified attention on waqf management systems, which continue to face challenges related to governance inefficiencies, limited public trust, and restricted global participation. Rapid advancements in digital technology, particularly blockchain, offer new opportunities to address these issues through decentralized, secure, and verifiable systems. This study aims to examine the potential of blockchain technology in enhancing transparency and promoting global social inclusion within waqf management. A qualitative research design combining doctrinal analysis and comparative evaluation is employed, utilizing secondary data from regulatory documents, institutional reports, and blockchain-based case implementations. Data are analyzed through thematic coding and comparative matrices to identify patterns and assess the effectiveness of technological integration. The findings reveal that blockchain significantly improves transparency, accountability, and donor participation by enabling immutable record-keeping and real-time tracking of waqf assets. Evidence also indicates that digital accessibility facilitated by blockchain expands cross-border engagement, strengthening the inclusivity of waqf systems. The study concludes that integrating blockchain into waqf management provides a viable pathway for modernizing Islamic philanthropic institutions, ensuring sustainable governance while enhancing global social impact.